Understanding the nature of ISIS - Shuriye, Abdi Omar (©Center for Promoting Ideas, USA, 2018)
Islam is a religion of peace and equilibrium; misguided Muslims are not. The predicament therefore lies on the line between these erroneous Muslims and the religion. Regrettably, this line is fashioned by this group of Muslims who interpret the religion based on their whims, interest and based on their limited knowledge. Yet, the saddest aspect of this is that majority of the Muslims worldwide are watching while insignificant group of senseless individuals act absurdly against them and their religion. In my view, all citizens of this beautiful universe share the blame of this mess; in fact, every one of us directly or indirectly is in a way part of this muddle. We have allowed dictators to oppress, invaded others and watched the killings of the innocent. ISIS could be said is the biggest entity of our life time on the line between extremism and moderation. It has gradually appeared and caught the world out of guard; by capturing the attention of the international community through barbarity and formation of its own state; changing the political map of the Middle East since the Sykes-Picot Agreement. Some observers have argued that ISIS appeared suddenly and out of nowhere; but in reality, it did not; in fact, nothing of this nature and magnitude comes out of the naught. On the contrary, ISIS is the product of the circumstances and times in the region and in the Muslim world; the pressure between wasatiyah and takfirism, between secular political outlook or ideologies and religious worldviews as well as between nationalism, nation state and khilafah political system. Add to this the dynamics of the region. Therefore, ISIS is a takfiri movement with political agenda, the chaos and civil war in Syria, the political disarray in Iraq, the American invasion, the attitude of Iran, the absolute monarchies in the Arabian Gulf, as well as the suppression of Arab spring all helped ISIS to become one of the politically most powerful jihadis movement.